2015
DOI: 10.1007/s11356-014-4061-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to pollutants in Madín Reservoir (Mexico) alters oxidative stress status and flesh quality in the common carp Cyprinus carpio

Abstract: Madín Reservoir (MR) is located on the Río Tlalnepantla in Mexico. Previous studies seeking to identify pollutants at this site evidence that MR water contains a considerable metal load as well as nonsteroidal anti-inflammatory drugs (NSAIDs) at concentrations above those determined suitable for aquatic life. This study aimed to evaluate whether chronic exposure to pollutants in MR alters oxidative stress status and flesh quality in muscle of the common carp Cyprinus carpio. The following biomarkers were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 70 publications
2
18
0
1
Order By: Relevance
“…Diclofenac also increased hepatic oxidative stress [18] in Hoplias malabaricus. Other studies have demonstrated similar effects of diclofenac on oxidative stress responses in Cyprinus carpio [3,19,20] and Danio rerio [21]. Hematological profiles were also altered in C. carpio [22] and Clarias gariepinus [23] as a result of diclofenac exposure.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Diclofenac also increased hepatic oxidative stress [18] in Hoplias malabaricus. Other studies have demonstrated similar effects of diclofenac on oxidative stress responses in Cyprinus carpio [3,19,20] and Danio rerio [21]. Hematological profiles were also altered in C. carpio [22] and Clarias gariepinus [23] as a result of diclofenac exposure.…”
Section: Introductionsupporting
confidence: 52%
“…Previous studies have shown that diclofenac exposure reduced nitric oxide production in primary cultures of leukocytes [16]. Other studies have demonstrated similar effects of diclofenac on oxidative stress responses in Cyprinus carpio [3,19,20] and Danio rerio [21]. Diclofenac also increased hepatic oxidative stress [18] in Hoplias malabaricus.…”
Section: Introductionmentioning
confidence: 79%
“…Fish muscle is easy to be subjected to oxidative stress, which results in the degenerative damage of flesh quality mainly by reducing muscle pH value, water holding capacity, and tenderness of fish [ 67 , 68 ]. Previous studies have indicated that flesh quality was closely related to antioxidant capacity [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers combined with metal body burdens of resident organisms have been widely used in aquatic pollution monitoring (Van der Oost et al 2003;Au 2004;Giarratano et al 2010;Duarte et al 2011;Oliva et al 2012Oliva et al , 2014Barhoumi et al 2014;Morachis-Valdez et al 2015), though most biomarker-based environmental quality studies were performed exclusively in highly anthropized sites (Malins et al 2006;Ramos-Gómez et al 2011;Ben Ameur et al 2012;Maranho et al 2012;Pereira et al 2014). We hypothesize that biomarkers are adequate for assessing the environmental quality of MPAs.…”
Section: Introductionmentioning
confidence: 97%